2023
DOI: 10.1097/ccm.0000000000006058
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Vital Organ Support Provided to ICU Patients*

Lucy J. Modra,
Alisa M. Higgins,
David V. Pilcher
et al.

Abstract: Objectives: Critically ill women may receive less vital organ support than men but the mortality impact of this differential treatment remains unclear. We aimed to quantify sex differences in vital organ support provided to adult ICU patients and describe the relationship between sex, vital organ support, and mortality. Design: In this retrospective observational study, we examined the provision of invasive ventilation (primary outcome), noninvasive ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…In our cohort, women less frequently received treatment with multiple vasoactive agents and interventions while in intensive care, yet no differences in ICU mortality or ICU LOS were observed. This aligns with a recent study in 699,535 ICU patients that reported an even lower overall hospital mortality in women despite significantly less organ support compared to men [ 42 ]. However, the impact of the sex-imbalance in provision of ICU care on long-term survival remains uncertain at this point.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our cohort, women less frequently received treatment with multiple vasoactive agents and interventions while in intensive care, yet no differences in ICU mortality or ICU LOS were observed. This aligns with a recent study in 699,535 ICU patients that reported an even lower overall hospital mortality in women despite significantly less organ support compared to men [ 42 ]. However, the impact of the sex-imbalance in provision of ICU care on long-term survival remains uncertain at this point.…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously claimed that women are less frequently admitted to ICUs [ 8 , 40 ] and undertreated compared to men, both before and during ICU admission, despite being equally or even more severely ill [ 3 , 8 , 41 , 42 ]. This included less use of mechanical ventilation and renal replacement therapy and earlier discharge from ICU [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data, albeit limited, point towards the direction of worse outcomes among men despite a more frequent use of advanced therapies in men compared to women. The latter is in accordance with other evidence of (i) gender discrimination in regards to the triage upon ICU admission (women are less frequently admitted to the ICU, as compared to men, despite more grave disease [26]), and (ii) a gender-driven differential in the treatment modalities offered to ICU patients (women have been found to receive less vital organ support within the ICU setting [27]). It is essential to emphasize that while our study does not specifically investigate gender discrimination in the ICU context, we contribute to the broader discussion on gender-related disparities in critical care.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to the results of experimental studies [116,117], a possible effect of the sexual hormones on the Doppler blood flow velocities in cerebral vessels in patients with aSAH could not be demonstrated [118]. Furthermore, sex-related differences in the management and delivery of care of patients with aSAH to the disadvantage of women-as already shown in other medical conditions-could play a role in the development of DCI, and these should be further investigated [119][120][121].…”
Section: Results In Contextmentioning
confidence: 67%